Coping strategies and their relationship with subjective distress due to the COVID-19 pandemic in Brazil - Alvares Duarte Bonini Campos, Juliana (2022)
Objectives: To identify the strategies used by Brazilian adults for coping with the COVID-19 pandemic and to verify the effect of these strategies on subjective distress. Methods: This was a cross-sectional observational study with online data collection in May/June 2020, November/December 2020, and May/June 2021. The BriefCOPE Inventory and the Impact of Event Scale (IES-R) were used. The prevalence of strategies used at different time points was estimated with a 95% confidence interval and compared with a z-test. A multiple logistic regression model was constructed and the odds ratio (OR, 95%CI) was calculated to verify the probability of subjective distress according to the coping strategy used. Results: Younger individuals had a lower prevalence of adaptive strategies, which increased significantly with age. Participants with higher income levels had a higher prevalence of adaptive strategies, as did those who were never diagnosed with a mental health disorder. The prevalence of using only maladaptive strategies ranged from 6.1% to 5.4% (p > 0.05). The use of problem-centered strategies (Active Coping and Planning), venting of emotions, and substance use increased with time, while acceptance and behavioral disengagement decreased. In general, the population used problem-centered strategies, but the high prevalence of problem avoidance was striking. Positive reinterpretation and acceptance were protective factors for subjective distress, whereas maladaptive strategies increased the chance of distress. The presence of a negative valence component (problem- or emotion-centered) increased the chance of subjective distress, whereas strategies based on Problem Solving acted as a protective factor. Conclusion: Coping strategies were significantly associated to subjective distress and have changed since the beginning of the pandemic. Strategies focused on emotion regulation may be relevant to minimize distress.